Penggunaan Pronomina Persona sebagai Bentuk Sapaan di Kalangan Remaja Sunda - Asri Soraya Afsari; Cece Sobarna (Badan Pengembangan dan Pembinaan Bahasa, 2024)
Adolescents have different characteristics compared to adults and children. They also have distinct addressing characteristics, especially among Sundanese adolescents. The shift and change in the use of personal pronouns as a form of address among Sundanese adolescents is an intriguing area for further study. Sundanese addresses are dynamic and evolve with the times and societal developments, including those among adolescents. This research uses descriptive and qualitative methods to use personal pronouns as an address among Sundanese adolescents. Data collection involved observation and recording of speech among male and female Sundanese adolescents, as well as interviews to gather additional information. The research was conducted in three stages: data collection, analysis, and presentation of the results. The study was centered in Bandung City and found that the personal pronoun